Consumers‘ Intention to Adopt Mobile Marketing in Rural Areas. The Case of South Region in Unguja - Nuru M., Haji; Kara, Nassra; Mohammed, Salum (European Scientific Journal, ESJ, 2023)
The explosive use of mobile phones facilitates the introduction of different mobile app services which become an essential part of daily life. This forces the business vendors to place individually targeted marketing messages through mobile phones to ensure easy access to the service since the mobile phone is in the hands of owner all the day long. Most of the studies in mobile marketing adoption focused on urban and university consumers. This study aims to investigate the perception of consumers in rural areas on their intention to adopt mobile phone applications such as mobile marketing. A cross-sectional survey was conducted to collect data through self-administered questionnaires to consumers in two villages in the South district of Unguja. Confirmatory factor analysis and Structural Equation modeling were used to test the relationship of the constructs on the extended TAM model. The results show that perceived usefulness, perceived ease of use, and facilitating conditions were the significant determinants of behavioral intention to adopt mobile marketing to consumers of rural areas. The Implications and limitations of the research were discussed.